2020
DOI: 10.5664/jcsm.8620
|View full text |Cite
|
Sign up to set email alerts
|

Performance of peripheral arterial tonometry–based testing for the diagnosis of obstructive sleep apnea in a large sleep clinic cohort

Abstract: Study Objectives: Peripheral arterial tonometry (PAT)-based technology represents a validated portable monitoring modality for the diagnosis of OSA. We assessed the diagnostic accuracy of PAT-based technology in a large point-of-care cohort of patients studied with concurrent polysomnography (PSG). Methods: During study enrollment, all participants suspected to have OSA and tested by in-laboratory PSG underwent concurrent PAT device recordings. Results: Five hundred concomitant PSG and WatchPat tests were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 22 publications
2
44
3
1
Order By: Relevance
“…Using a 3% desaturation threshold for both peripheral arterial tone AHI and AHI, we found that 20% of the PAT studies overestimated by > 15 events/h and 9% underestimated by > 15 events/h, leading to clinically relevant misclassifications in both directions. 2 Dr. Cook states that the accuracy of 53% in our study represents "a finding that differs significantly from all other published PAT AHI validation studies that reflect correlation above 85%." 1,[3][4][5][6] The reader must be cautioned about this statement, because the existing literature may show a much more nuanced view.…”
contrasting
confidence: 84%
See 3 more Smart Citations
“…Using a 3% desaturation threshold for both peripheral arterial tone AHI and AHI, we found that 20% of the PAT studies overestimated by > 15 events/h and 9% underestimated by > 15 events/h, leading to clinically relevant misclassifications in both directions. 2 Dr. Cook states that the accuracy of 53% in our study represents "a finding that differs significantly from all other published PAT AHI validation studies that reflect correlation above 85%." 1,[3][4][5][6] The reader must be cautioned about this statement, because the existing literature may show a much more nuanced view.…”
contrasting
confidence: 84%
“…The argument that one's PSG pulse oximeter "lacks accuracy" does not hold water even without any further analyses, because this type of unidirectional, systematic error would lead to either consistent overestimation or predominant underestimation of the results by PAT vs gold-standard, supervised, and curve-verified PSG oximetry. However, this situation is not what was found in the PATER study, 2 where there were significant percentages of both false alarm and false reassurance. If one compares the mean/median/interquartile range/90th percentile of the hypoxic burden (percentage of total sleep time with SpO 2 < 90%), the results show 11/2/0-10/40% vs 4/0.2/0-2/10% using PSG vs PAT, respectively, or a significantly higher value using PSG (Wilcoxon signed rank test, P < .0001).…”
contrasting
confidence: 70%
See 2 more Smart Citations
“…4 In this issue of the Journal of Clinical Sleep Medicine, Ioachimescu and colleagues performed concurrent laboratory-based polysomnography and WatchPAT-200 studies comprising 500 veterans, demonstrating that differences in severity levels between the two studies occurred in a sizeable number of patients. 5 The authors noted that 5% of patients with a WatchPAT-based diagnosis of moderate or severe OSA who did not have OSA on laboratory-based polysomnography and the 20% of patients with WatchPAT-diagnosed mild OSA who had moderate or severe OSA on laboratory-based polysomnography. It is of concern that these erroneous diagnoses can lead to poor patient outcomes, either related to potential mistreatment or nontreatment.…”
mentioning
confidence: 99%